MODERATING ROLE OF COPING STRATEGIES IN RELATIONSHIP BETWEEN HOUSEHOLD CHAOS AND SOCIAL ADAPTIVE FUNCTIONING OF ADOLESCENTS - Rehman, Sadia; Aziz, Sadia; Dogar, Imtiaz Ahmed (Journal of Pakistan Psychiatric Society, 2025)
ABSTRACT OBJECTIVE To examine the interplay between the house hold chaos, social adaptive functioning and coping among adolescents. STUDY DESIGN Cross-sectional research design. PLACE AND DURATION OF THE STUDY The study was conducted at IIU during June 2020 to January 2021. SUBJECTS AND METHODS 400 participants between age 10 to 19 years were selected through convenience sampling technique to participate in the study. Confusion, Hubbub and Order Scale (CHAOS), Child and Adolescents Social Adaptive Functioning Scale (CASAFS), and Brief Cope Scale (BCS) along with demographic sheet were used to collect data on the variables understudy. RESULTS Results revealed that as the household chaos increases the social adaptive functioning decreases (r=-.33**). The results of findings depict that problem-focused coping buffer the effect of household chaos on school performance (R2=.31, ∆R²=.30, p<.05) and on home duties /self-care (R2=.23, ∆R²=.22, p<.05). Results of emotion-focused coping revealed that EFC buffer the effect of household chaos on peer relationship (R2=.23, ∆R²=.22, p<.05) and on family relationship (R2=.33, ∆R²=.32, p<.05). CONCLUSION House hold chaos, social adaptive functioning and coping has an interdependent relationship among adolescents. Increased household chaos predicted decline in social adaptive functioning while coping played a moderating role between these two factors. KEY WORDS Household Chaos, Social Adaptive Functioning, Coping Strategies, Adolescents